After the Flood: Reflections of a Wounded Healer's Countertransference in Adolescent Treatment. - Cuseglio, Ralph (Clinical Social Work Journal, 2021)
The aim of this paper is to analyze countertransference experienced by a therapist while treating a 'difficult to treat' adolescent client. In doing so, the therapist discusses how his childhood experiences and the subsequent assumption of Carl Jung's wounded healer archetype fueled the countertransference in ways that were concurrently beneficial and detrimental to treatment. The client's symptoms, behavior, and family system are also examined to illustrate how they uniquely contributed to the intense feelings evoked in the therapist. Topics of omnipotence, curative fantasies, biblical myth, and childhood trauma are explored throughout this paper, as they uniquely intersected to create a complex web of psychodynamics between therapist and client. This is demonstrated primarily through an interpretation of the client's final session and the therapist's dream following treatment. The therapist shares reflections of the treatment, implications for wounded healer self-disclosure, as well as the archetype's importance to the social work profession.